2015
DOI: 10.15376/biores.10.2.2809-2822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Oxide Treatment on the Properties of Cellulose Nanofibril Films Made of Banana Petiole Fibers

Abstract: In this study, banana petiole-based cellulose nanofibril (CNF) films treated with graphene oxide (GO) were prepared and evaluated by means of Fourier-transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), dynamic mechanical analysis (DMA), and thermogravimetric analysis (TGA). Tensile strengths (TS), dynamic mechanical properties, and thermal stabilities of the films were affected positively when the GO loading was less than 4.4 wt%. From these results, FTIR spectra, and SEM analyses, a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…On the other hand, cellulose has a sharp peak near wave number of 1000 cm −1 , which is related to bending vibrations of O─H groups. Moreover, the peak at 1700 cm −1 is related to C═O groups of cellulose . The FTIR spectra of synthesized GO is also presented in Figure to compare the three existing phases.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, cellulose has a sharp peak near wave number of 1000 cm −1 , which is related to bending vibrations of O─H groups. Moreover, the peak at 1700 cm −1 is related to C═O groups of cellulose . The FTIR spectra of synthesized GO is also presented in Figure to compare the three existing phases.…”
Section: Resultsmentioning
confidence: 99%
“…Xu, Wang [88] analyzed Graphene oxide Crystal Nanofibril treated films SEM analysis has been carried out after 45 mins of ultrasonication and it has been observed that SEM picture examinations delineated that the GO was scattered generally inside the CNF grid after ultrasonication and that the GO communicated with CNF through intermolecular bonds. Durge, Kshirsagar [77] studied that graphene suspension probe which was sonicated for 120 mins displayed less layer of graphene nanosheets whereas bath sonicated for 60 mins showed more graphene nanosheets.…”
Section: Effect Of Ultrasonication On Graphene Nanofluidsmentioning
confidence: 99%
“…These residues represent a serious pollution problem as it is dispersed in the planting area or burned. Due to the increase in the number of banana processing industries, there is a massive increase in the accumulation of banana wastes which necessitates the development of proper strategies to reuse these residues (Happi Emaga et al, 2007Memon et al, 2008;Xu et al, 2015).…”
Section: Bananamentioning
confidence: 99%